Critical review of the threats affecting the building of critical infrastructure resilience. (15th June 2021) - Osei-Kyei, Robert; Tam, Vivian; Ma, Mingxue; Mashiri, Fidelis
Abstract: In modern society, critical infrastructures (CIs) resilience has become a critical issue in crisis management and CIs protection. However, various threats/hazards could lead to disruption and failure of developing CIs resilience, which inevitably can lead to negative repercussions to humanity and national economy. In this regard, detailed understanding of the threats/hazards and their impacts are critical to improve a country's preparedness for unexpected situations such as the COVID-19 pandemic. This paper aims to conduct a critical analysis of the potential threats to governments' efforts and capacity to build CI resilience. A three-stage systematic review process is adopted and a total of 35 papers are carefully selected. Results show that during the past two decades, researchers' interest in exploring the threats/hazards in CIs resilience has increased. Further, most of the research publications emanate from the United States and United Kingdom. Lastly, a total of 31 threats/hazards are identified, with the most reported threats/hazards being: (1) natural disasters, (2) ageing and decay, (3) cyber threats, (4) terrorist activities, (5) contamination and (6) cascading failure/threat. The findings of this study provide a solid foundation for future research on developing CIs resilience. Additionally, the findings will inform policy makers and government authorities of the salient threats affecting the building of CIs resilience. Highlights: In modern society, critical infrastructures (CIs) resilience has become a critical issue in crisis management. This paper aims to conduct a critical analysis of the potential threats/hazards affecting the building of CIs resilience. A three-stage systematic review process is adopted. Results show that during the past two decades, researchers' interest in exploring the threats/hazards affecting the building of CIs resilience has increased. 31 threats/hazards are identified, with the most reported threat being natural disasters,